Sample Preparation Techniques for Chemical Analysis - Kaykhaii, Massoud (IntechOpen, 2021)
Despite having powerful software, microchips, and solid-state detectors that enable analytical chemists to achieve fast, stable, and accurate signals from their instruments, sample preparation is the most important step in chemical analysis. Issues can arise at this step for various reasons, including a low concentration of analytes, incompatibility of the sample with the analytical instrument, and matrix interferences. This volume discusses the basics of sample preparation and examines modern techniques that can be used by both novice and expert analytical chemists. Chapters review microextraction, surface spectroscopy analysis, and techniques for particle, tissue, and cellular separation.